1996
DOI: 10.1300/j077v14n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment Among Husbands of Women with Breast Cancer

Abstract: T h c cffcct o f marital support and support from other adults on the emotional and physical adjustment of 121 husbands of women with brcast cancer was examined. Role function and satisfaction with health care also were evaluated as predictors of adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 16 publications
4
22
0
2
Order By: Relevance
“…Similar to other studies [11,33,13,10], all male partners in this study reported a wide range of emotional responses to their wife's diagnosis. For these partners, their wife's diagnosis resulted in a 'change in status', engulfing him in stressful thoughts and emotions.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to other studies [11,33,13,10], all male partners in this study reported a wide range of emotional responses to their wife's diagnosis. For these partners, their wife's diagnosis resulted in a 'change in status', engulfing him in stressful thoughts and emotions.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, marital status and spousal/partner relationships to the patient were associated with lower psychological, and spiritual scores for cancer caregivers, which supports the findings of previous cancer caregiver research. [16][17][18][19] Further studies are needed to compare differences in quality of life for AIDS and cancer caregivers. Interestingly, based on the Spiritual Well-being Scale (SWBS), 42 which was also administered in this current study and is discussed in another article, 43 AIDS caregivers were found to have lower spiritual well-being than cancer caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…14 In a study of family members of patients during the terminal phase of illness, Kristjanson et al 15 found that family members' scores on the Health Index were significantly lower than normative scores based on a healthy population. Several studies have also shown that the spouse of a patient with cancer experiences levels of distress at least as severe as that of his or her partner when the disease is advancing, [16][17][18][19] and that caregivers of terminally ill family members experienced distress 1 year after diagnosis with a significant decline in their mental health. 20 Such studies indicate the palliative care needs of family caregivers across the illness experience.…”
mentioning
confidence: 99%
“…One such study found that role strain correlated with emotional distress at 6 different time points, ranging from 7 to 10 days after a wife's breast surgery to 1 year later. 27 However, the relationship of role strains to distress was examined with crosssectional analyses rather than longitudinally to determine the predictive value of role strain across time.…”
Section: Secondary Role Strainsmentioning
confidence: 99%